HOW SELF-EFFICACY, MOTIVATION, AND LEARNING STRATEGIES CORRELATE WITH STUDENTS' ACADEMIC ACHIEVEMENT - khoyrul umam syarif (Graduate Program, University of Islam Malang, 2020)
The intention of this research to scrutinize the correlation Among Self-Efficacy, Motivation, and Learning Strategies, which correlated on Academic Achievement. Every learner has Potential ability to be a success using their capabilities. In this study, the researcher used descriptive quantitative method and a correlation research design. It used multiple regression analysis by using SPSS 16.0 to correlates the most significant on student academic Achievement. 114 students were recruited. It was located in Pamekasan Madura. The researcher used a descriptive quantitative method and a correlation research design with multiple regression analysis. This study investigates the predictor variable X1 (Self-Efficacy), X2 (Motivation), X3 (learning strategy), X4 (the strongest variable Self-Efficacy, Motivation, and Learning Strategies), X5 (simultaneous correlation Self-Efficacy, Motivation, and Learning Strategies) and criterion variable Y (Academic Achievement). The researcher used two types collecting the data’s that are questionnaire and summative test in the final examination. Keywords: Self-Efficacy, Motivation, Learning Strategies, Academic achievement.